2012
DOI: 10.1088/1674-1056/21/8/083401
|View full text |Cite
|
Sign up to set email alerts
|

Study of (e, 2e) process on potassium at 6 eV–60 eV above threshold in a second-order Born approximation

Abstract: The standard distorted wave Born approximation (DWBA) method has been extended to second-order Born amplitude in order to describe the multiple interactions between the projectile and the atomic target. Second-order DWBA calculations have been preformed to investigate the triple differential cross sections (TDCS) of coplanar doubly symmetric (e, 2e) collisions for the alkali target potassium at excess energies of 6 eV–60 eV. Compared with the previous first-order DWBA calculations, the present theoretical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…We recently extended the standard DWBA method by treating the projectile-target interactions up to the secondorder Born amplitude to improve the description of complicated projectile-target interactions. We investigated the coplanar symmetric (e, 2e) process of one-valence-electron targets Na and K, [18,19] and reasonable agreements with experiment were obtained. Hitawala et al [16] observed in their research that the ratio of forward to backward peak decreased for Mg and Ca in comparison to Na and K, which showed the secondorder effects were more involved in the ionization of alkali earth atoms.…”
Section: Introductionmentioning
confidence: 59%
“…We recently extended the standard DWBA method by treating the projectile-target interactions up to the secondorder Born amplitude to improve the description of complicated projectile-target interactions. We investigated the coplanar symmetric (e, 2e) process of one-valence-electron targets Na and K, [18,19] and reasonable agreements with experiment were obtained. Hitawala et al [16] observed in their research that the ratio of forward to backward peak decreased for Mg and Ca in comparison to Na and K, which showed the secondorder effects were more involved in the ionization of alkali earth atoms.…”
Section: Introductionmentioning
confidence: 59%
“…On the theoretical side, a great deal of calculations have been carried out [8][9][10][11][12][13][14] for this particular process. For example, the nonperturbative convergent close-coupling (CCC) method, [15,16] which produces reliable results, has been successfully extended to calculate the triply differential cross sections for electron, sodium ionization by Bray et al [8] and the perturbative distorted wave Born approximation (DWBA) have also been used to study the problem of electron, complex targets ionization by Srivastava et al, [9] Hitawala et al, [10] Khajuria et al, [11] and Zhou et al [12][13][14] Although their results qualitatively reproduced many features of the cross section and are in agreement with the experimental results of Murray, [7] significant discrepancies can still be noticed.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Total cross section of ionization is closely proportional to the imaginary part of the momentum space optical potential. This method has been used in predicting the ground-state ionization cross sections for electron scattering from various targets, [20][21][22][23][24][25][26] and the positron scattering from atoms. [27,28] The approach allows for a straightforward extension to the calculation of cross sections for ionization from metastable excited levels.…”
Section: Introductionmentioning
confidence: 99%